2017
DOI: 10.1016/j.jacc.2017.01.064
|View full text |Cite
|
Sign up to set email alerts
|

The Aging Cardiovascular System

Abstract: Cardiovascular disease (CVD) presents a great burden for elderly patients, their caregivers, and health systems. Structural and functional alterations of vessels accumulate throughout life, culminating in increased risk of developing CVD. The growing elderly population worldwide highlights the need to understand how aging promotes CVD in order to develop new strategies to confront this challenge. This review provides examples of some major unresolved clinical problems encountered in daily cardiovascular practi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
166
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 432 publications
(200 citation statements)
references
References 156 publications
4
166
0
2
Order By: Relevance
“…In vitro experiments show that this metabolic phenotype leads to activation of a pathway involving mitochondrial oxidative stress (mitoOS) and pyruvate kinase M2-mediated STAT3 activation, resulting in increased production of pro-atherogenic IL-6 and IL-1β. Other studies have suggested additional links between mitoOS and human CAD (Paneni et al, 2017), and mitoOS in macrophages increases plaque progression, activates macrophage NF-κB, and promotes the formation of potentially atherogenic neutrophil extracellular traps (NETs) in mouse models of atherosclerosis (Wang et al., 2014; Wang et al, 2017). …”
Section: Energy Metabolism Affects Immune Cell Function In Atherosclementioning
confidence: 99%
“…In vitro experiments show that this metabolic phenotype leads to activation of a pathway involving mitochondrial oxidative stress (mitoOS) and pyruvate kinase M2-mediated STAT3 activation, resulting in increased production of pro-atherogenic IL-6 and IL-1β. Other studies have suggested additional links between mitoOS and human CAD (Paneni et al, 2017), and mitoOS in macrophages increases plaque progression, activates macrophage NF-κB, and promotes the formation of potentially atherogenic neutrophil extracellular traps (NETs) in mouse models of atherosclerosis (Wang et al., 2014; Wang et al, 2017). …”
Section: Energy Metabolism Affects Immune Cell Function In Atherosclementioning
confidence: 99%
“…Inflammatory conditions are substantially involved in the development of endothelial dysfunction, 53 where IL-1β (interleukin-1β) is one of the key proinflammatory cytokines. Honda et al 54 demonstrated a close relationship between endothelial dysfunction evaluated by flow-mediated dilation and vascular inflammation detected by ( 18 F)-fluorodeoxyglucosepositron emission tomography/computed tomography in subjects with mild cardiovascular risks, both of which were improved after a 6-month antihypertensive treatment.…”
Section: Hallmark Of Disease Inflammationmentioning
confidence: 99%
“…Arterial stiffness results primarily from loss of elastic fibers and an increase in collagen (Fritze et al, 2012). Like AD, cardiovascular disease is another aging‐related disease that brings a great burden for the patients and healthcare systems (Paneni, Diaz Cañestro, Libby, Lüscher, & Camici, 2017). …”
Section: Systems Level Events In Aging and Admentioning
confidence: 99%